Regional patterns in cause-specific mortality in Montenegro, 1991–2019 - Raičević Đoko; Arsenović Daniela (Open Geosciences)
This study examines regional mortality trends in Montenegro over the past three decades (1991–2019), focusing on the three leading causes of death: circulatory diseases, neoplasms, and ill-defined conditions. Mortality data were obtained from the Statistical Office of Montenegro (MONSTAT) and the Institute of Public Health of Montenegro. Analysis was performed using crude death rate by cause of death for three regions in Montenegro. Health (doctors and hospital beds per 10,000 inhabitants) and socio-economic indicators (GINI coefficient and Human Development Index) were sourced from the World Health Organization database. A structured three-stage analytical approach was employed to investigate regional patterns and determinants of cause-specific mortality: descriptive statistics and trend analysis using linear regression, t-test, and multiple linear regression. Circulatory diseases account for the highest proportion of deaths (42%), followed by neoplasms (17%) and ill-defined causes (15%), with all other causes contributing to the remaining 25%. The analysis reveals significant and persistent regional disparities in cause-specific mortality, with south–north gradient in mortality observed for circulatory diseases and neoplasms, while ill-defined conditions displayed a reversed north–south pattern. These patterns have remained relatively stable over time. Furthermore, multiple linear regression analysis underscores the influence of health and socio-economic factors on regional mortality variation. The findings highlight the urgent need for spatially targeted public health interventions, particularly those aimed at addressing noncommunicable disease risk factors. Integrating geographic and public health approaches offers a critical pathway for reducing mortality disparities and improving population health outcomes in Montenegro.